Evaluation of environmental and economic benefits of CO_2 utilization technologies and their future development trends - YANG Gang; WANG Chenxi; LUO Chunlin; GUO Zeyu; LIU Min; ZHANG Honglei; XU Mengxia; WU Tao* (能源环境保护)
In 2022, global CO_2 emissions reached 36.07 Gt, but only 230 Mt of CO_2 were captured and utilized, accounting for just 0.64% of the total emissions. To achieve the ambitious goal of carbon neutrality by 2060, CO_2 emissions must be reduced to 5 Gt, with CO_2 utilization reaching a total of 1.2 Gt, representing a utilization rate of 24%. This highlights the urgent need to enhance CO_2 utilization. Carbon capture, utilization, and storage (CCUS) technology is considered one of the most promising solutions for mitigating CO_2 emissions in addressing the urgent global challenges posed by climate change. The transformation of captured CO_2 into value-added industrial products (CCU) through various chemical, biological, and electrochemical processes has been a core focus of both academic and industrial research. Despite the focus on CCU, the precise contribution of various conversion technologies to reducing CO_2 emissions remains unclear. To address this issue, this paper systematically reviews the developmental landscape of CO_2 conversion technologies over recent decades, with a particular focus onthree representative CO_2 conversion pathways and their resulting products. Through a comprehensive analysis, the paper conducts a comparative assessment of the environmental impacts and technical economics associated with distinct technology pathways and products. The discussion further explores the potential applications of these conversion technologies and their capacity to achieve negative carbon emissions. Crucially, the research highlights the substantial potential for achieving negative carbon emissions, thereby playing a pivotal role in the overall reduction of CO_2 emissions. In conclusion, this paper not only provides insights into the current state of CO_2 conversion technologies but also emphasizes the crucial role of carbonation and polymerization products in achieving significant reductions in carbon emissions.